Byzantine Narrative : Papers in Honour of Roger Scott - BRILL (Byzantina Australiensia Ser, 2017)
"Byzantine Narrative: Papers in Honour of Roger Scott" -- "Copyright" -- "Dedication" -- "Contents" -- "Introduction" -- "Roger Scott" -- "List of Illustrations" -- "KEYNOTE PAPERS" -- "Novelisation in Byzantium: Narrative after the Revival of Fiction" -- "Narrating Justinian: From Malalas to Manasses" -- "NARRATIVE IN HISTORIANS, CHRONICLES & FICTION" -- "To Narrate the Events of the Past: On Byzantine Historians, and Historians on Byzantium" -- "Tradition and Originality in Photius' Historical Reading" -- "Narrating the Trials and Death in Exile of Pope Martin I and Maximus the Confessor" -- "The Use of Metaphor in Michael Psellos' Chronographia" -- "War and Peace in the Alexiad" -- "Moralising History: the Synopsis Historiarum of John Skylitzes" -- "The Representation of Augustae in John Skylitzes' Synopsis Historiarum" -- "The Madrid Skylitzes as an Audio-Visual Experiment" -- "The Goths and the Bees in Jordanes: A Narrative of No Return" -- "From 'Fallen Woman' to Theotokos: Music, Women's Voices and Byzantine Narratives of Gender Identity" -- "How the Entertaining Tale of Quadrupeds became a Tale: Grafting Narrative" -- "Lamenting the Fall or Disguising a Manifesto? The Poem Conquest of Constantinople" -- "A Probable Solution to the Problem of the Chronicle of the Turkish Sultans" -- "NARRATIVE IN BYZANTINE ART" -- "The Narration of Christ' s Passion in Early Christian Art" -- "Observations on the Paintings of the Exodus Chapel, Bagawat Necropolis, Kharga Oasis, Egypt" -- "The Column of Arcadius: Retlections of a Roman Narrative Tradition" -- "Biblical Narrative in the Mosaics of Bishop Theodore's Cathedral, Aquileia" -- "Plato, Plutarch and the Sibyl in the Fresco Decoration of the Episcopal Church of the Virgin LjeviÅ¡ka in Prizren" -- "Narrativity in Armenian Manuscript Illustration".